Analisis Faktor-faktor yang Mempengaruhi Kurs dan Jumlah Uang Beredar di Indonesia - Oktavia, Adek Laksmi (Jurusan PIPS FKIP UMMY Solok, 2016)
This article focused on analyze (1) Effect of the money supply, income, domestic interest rates, inflation and the trade balance to the exchange rate in Indonesia. (2) The influence of domestic interest rates, output and the exchange rate on the money supply in Indonesia. Data used time series of (I year quartal 2000 – IV year quartal 2010). This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS). The result of research concludes that (1) the money supply have a significant and positive impact on the exchange rate, incomes have significant and positive impact on the exchange rate, domestic interest rates significantly and negatively on the exchange rate and inflation have a significant and positive impact on the exchange rate. While the trade balance is not significant and negative effect on the exchange rate in Indonesia. If the money supply increases, the exchange rate will also increase or depreciate. If income increases, the exchange rate will depreciate. If the domestic interest rate increases, the exchange rate will appreciate. If inflation increases, the exchange rate will also depreciate. (2) domestic interest rates, output, and the exchange rate significantly influence the money supply in Indonesia.